Gastric Anisakiasis Masquerading as Gastroesophageal Reflux Disease. (8th February 2023) - Groudan, Kevin; Martins, Tiago; Schmelkin, Ira J.
Abstract : Anisakiasis of the gastrointestinal tract is caused by the consumption of raw or undercooked seafood infected with Anisakis larvae. Penetration of Anisakis larvae into the gastrointestinal mucosa leads to severe epigastric pain, nausea, and vomiting, usually within hours of ingestion of the parasite. Suspicion for gastrointestinal Anisakiasis should be raised in patients with a compatible dietary history. Definitive diagnosis can be made by direct visualization of larvae via endoscopic examination. Although symptoms are self-limiting, the removal of larvae by gastroscopy can hasten relief of symptoms. There are a large number of cases of gastric anisakiasis reported from Japan, Korea, and Western Europe, where it is customary to consume raw fish. Cases reported from the United States are less common, and given the nonspecific symptoms of anisakiasis, the diagnosis can be missed. We report a patient who presented with gastroesophageal reflux disease like symptoms that started after ingesting raw fish. He was found by esophagogastroduodenoscopy to have white, filiform worms penetrating into the wall of his stomach, consistent with a diagnosis of gastric anisakiasis.